2016
DOI: 10.4268/cjcmm20162207
|View full text |Cite
|
Sign up to set email alerts
|

Advance in flavonoids biosynthetic pathway and synthetic biology

Abstract: Flavonoids are the valuable components in medicinal plants, which possess a variety of pharmacological activities, including anti-tumor, antioxidant and anti-inflammatory activities. There is an unambiguous understanding about flavonoids biosynthetic pathway, that is,2S-flavanones including naringenin and pinocembrin are the skeleton of other flavonoids and they can transform to other flavonoids through branched metabolic pathway. Elucidation of the flavonoids biosynthetic pathway lays a solid foundation for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In this study, we observed distinct gene expression profiles among three ESMs from Hubei, Jiangxi, and Anhui, with particular attention to the AHHS from Anhui, which exhibited the lowest flavonoid levels ( Figure 2C ). Despite identifying differential gene expression in AHHS compared to the other two ESMs, the majority of flavonoid biosynthesis-related genes detected did not elucidate the precise causes of the varied metabolite accumulation ( Zou et al., 2016 ; Liu et al., 2021 ; Lou et al., 2021 ). Two primary reasons are posited: (1) the complete biosynthetic pathways of major flavonoids such as icariin and epimedin remain elusive to date ( Huang et al., 2015 ; Wang et al., 2021 ), precluding the direct detection of gene expression responsible for their biosynthesis; (2) the absence of a reference genome for ESMs hinders the examination of genomic variations among these samples.…”
Section: Discussionmentioning
confidence: 93%
“…In this study, we observed distinct gene expression profiles among three ESMs from Hubei, Jiangxi, and Anhui, with particular attention to the AHHS from Anhui, which exhibited the lowest flavonoid levels ( Figure 2C ). Despite identifying differential gene expression in AHHS compared to the other two ESMs, the majority of flavonoid biosynthesis-related genes detected did not elucidate the precise causes of the varied metabolite accumulation ( Zou et al., 2016 ; Liu et al., 2021 ; Lou et al., 2021 ). Two primary reasons are posited: (1) the complete biosynthetic pathways of major flavonoids such as icariin and epimedin remain elusive to date ( Huang et al., 2015 ; Wang et al., 2021 ), precluding the direct detection of gene expression responsible for their biosynthesis; (2) the absence of a reference genome for ESMs hinders the examination of genomic variations among these samples.…”
Section: Discussionmentioning
confidence: 93%
“…It serves as the main route for flavonoid biosynthesis, with the majority of flavonoids and dihydroflavonoids being synthesized through this pathway. On the other hand, the phenylalanine metabolic pathway offers an alternate route for the biosynthesis of specific isoflavonoids and flavonol compounds [20,21]. The biosynthesis of flavonoid compounds is tightly regulated by various biosynthetic enzymes and genes, including PAL, 4CL, CHS, FLS, and F3 ′ H [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…In the flavonoid biosynthesis pathway of sample S8, C4H catalyzed the production of coumaroyl-CoA, CHS facilitated chalcone formation, and naringenin is produced by isomerization of CHI. Dihydroflavonoids are crucial precursors of flavonoids [38][39][40]. Up-regulation of the aforementioned genes in the flavonoid biosynthesis pathway of sample S8 promoted the accumulation of dihydro flavonoids and facilitated the production of isoflavones, flavones, and dihydro flavanols under the catalysis of various enzymes, consequently increasing flavonoid content.…”
Section: Discussionmentioning
confidence: 99%